2020
DOI: 10.18203/2394-6040.ijcmph20204386
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patient related factors on health seeking behaviours among men with lower urinary tract symptoms attending surgical outpatient clinic at Meru Level Five Hospital, Kenya

Abstract: Background: Currently there are increased cases of men presenting with lower urinary tract symptoms (LUTS) especially in low resource countries. The purpose of this study was to establish the influence of patient related factors on health seeking behaviors for LUTS among men attending surgical outpatient clinic at Meru hospital, Kenya.Methods: Descriptive cross-sectional study design was used. Population involved 120 men suffering from LUTS, 2 physicians and 2 nurses. Questionnaires and interview guides were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…This was similar to study done in Meru Kenya on patient related factors influencing health seeking behavior among men suffering from LUTS which revealed that 78.6% (p<0.001) of the respondents agreed that lack of funds to cater for health care bill impended them from seeking health care. 11 This was also congruent to a study done on clinical care for patients with LUTS, which showed that high health care cost was associated with the low health seeking behavior. 12 Men who indicated that distance from their home to health care facility was not long were 2.21 [95% CI=1.01-4.84, p=0.047] times more likely to have high health seeking behavior compared to men who indicated that there was long distance to health care facility.…”
Section: Discussionsupporting
confidence: 80%
“…This was similar to study done in Meru Kenya on patient related factors influencing health seeking behavior among men suffering from LUTS which revealed that 78.6% (p<0.001) of the respondents agreed that lack of funds to cater for health care bill impended them from seeking health care. 11 This was also congruent to a study done on clinical care for patients with LUTS, which showed that high health care cost was associated with the low health seeking behavior. 12 Men who indicated that distance from their home to health care facility was not long were 2.21 [95% CI=1.01-4.84, p=0.047] times more likely to have high health seeking behavior compared to men who indicated that there was long distance to health care facility.…”
Section: Discussionsupporting
confidence: 80%
“…In Pakistan, more than half of the participants in a cross-sectional study had heard about PCa but only less than a quarter knew about its diagnostic test. 10 In Turkey, Imams demonstrated poor knowledge of PCa. 11 In rural parts of Kenya, more than three-quarters of men had heard about PCa but less than half were aware of its screening which resulted in a low level of general awareness of PCa .…”
Section: Introductionmentioning
confidence: 99%
“…5 Literature indicates that factors such as economic status, education level, knowledge and distance to health facilities influence health seeking behaviour. 6 Based on data obtained from health information system indicates that in Imenti North Sub county there were 3,593 cases of hypertension reported in 2013, 4419 cases in 2014, 3774 cases in 2015, 3,728 cases in 2016 and 2570 cases in 2017. This shows that the number of individuals suffering from hypertension has been persistently high.…”
Section: Introductionmentioning
confidence: 99%